The Influence of Product Placement and Event Sponsorship on Brand Awareness (A Study on Kopiko Products in the Korean Drama Vincenzo) - Laela Isnaeni; Mutia Febriani; Athiyatul Aula; Tiara Muthiarsih (Indonesian Journal of Business Analytics, 2024)
Korean culture has emerged and become a phenomenon of Asian-style globalization that has boomed in the last decade, particularly in the Korean drama industry. In the current Korean industry, a coffee candy brand that has won the hearts of coffee lovers, namely Kopiko, represents a phenomenon of a local product going international. The purpose of this study is to determine the influence of product placement and event sponsorship on the brand awareness of Kopiko products in the drama Vincenzo. This study employs quantitative data analysis methods using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 software. Primary data were collected by distributing questionnaires to 100 viewers of the drama Vincenzo in Cirebon. The results showed that product placement has a positive and significant effect on brand awareness, as does event sponsorship. It is important to explore other variables that can contribute to this goal. Future researchers should investigate these variables further.